Peran artificial intelligence dalam menggantikan tenaga kerja manusia: kajian menurut peraturan pemerintah no. 33 tahun 2013 tentang perluasan kesempatan kerja - Elfarani, Sania (Maliki Interdisciplinary Journal, 2026)
The rapid advancement of Artificial Intelligence (AI) technology in Indonesia’s industrial sector presents both opportunities and challenges for the workforce. This study aims to analyze the impact of AI implementation on employment and its alignment with the provisions of Government Regulation No. 33 of 2013 concerning the Expansion of Employment Opportunities. Although AI has the potential to replace human labor, particularly in routine activities, which may lead to an increase in unemployment, this technology also creates new job opportunities that require advanced skills and creativity.The research utilizes a normative juridical method through an analysis of relevant laws and regulations, particularly Law No. 13 of 2003 on Manpower and Government Regulation No. 33 of 2013. The study examines both primary and secondary legal materials to assess the adequacy of regulations in ensuring the protection of workers’ rights in the era of digitalization. The findings indicate that AI can improve efficiency and productivity; however, automation carries the risk of reducing the number of available jobs. Therefore, comprehensive policies and training programs are required to prepare the workforce for these changes. This study emphasizes the importance of establishing specific regulations related to AI and developing training initiatives as government strategies to guarantee legal protection and the welfare of workers in the technological era.